Purification and Application of Lipases from Pseudomonas Species: Lipases from Pseudomonas Species (Biological Sciences - PJSIR, 2016)
Lipases are important hydrolytic enzymes that hydrolyze long chain triacylglycerol intodiacylglycerol, monoacylglycerol, glycerol and fatty acids. Lipases are found in microorganisms, fungi,plants and animals. Commercially, useful extracellular lipases are isolated from different bacterial species,including Bacillus, Achromobacter, Alcaligenes, Arthrobacter, Pseudomonas, Staphylococcus andChromobacterium species. Among the Pseudomonas species, Pseudomonas aeruginosa, P. cepacia andP. fluorescence are the major producers of lipases. Bacterial lipases have great industrial applicationsbecause of their stability, selectivity and broad substrate specificity. Due to their large scale applicationin industrial sectors, attention is given to isolate Pseudomonas lipases. In this review, purification strategiesfor lipases isolated from Pseudomonas species have been focussed.